2012
DOI: 10.2495/sc120101
|View full text |Cite
|
Sign up to set email alerts
|

Eco-city indicators: governance challenges

Abstract: According to the most recent (2011) global census of eco-city initiatives, there are currently 178 eco-city initiatives under development, representing a significant mainstreaming of urban sustainability in the last decade. As the number of eco-city initiatives grows, so the question of how to define eco-city indicators and establish standards becomes more pressing. While there are many sustainability standards and certification schemes available for use at building level (e.g. LEED, BREEAM), similar sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The methodologies presented here, developed in collaboration with local experts and stakeholders, aim at contributing to the practical debate on the mainstreaming of ecocities. They can also complement the definition of ecocity indicators proposed by authors like Joss as a tool to support governance and a necessary step towards establishing common standards for urban sustainability [34].…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies presented here, developed in collaboration with local experts and stakeholders, aim at contributing to the practical debate on the mainstreaming of ecocities. They can also complement the definition of ecocity indicators proposed by authors like Joss as a tool to support governance and a necessary step towards establishing common standards for urban sustainability [34].…”
Section: Discussionmentioning
confidence: 99%
“…Joss et al [9] have identified the basic problem which causes insufficient patronising of public transport. They [9] suggested a maximum 300m distance of pedestrian travel to access public transport.…”
Section: Public Transportmentioning
confidence: 99%
“…Joss et al [9] have identified the basic problem which causes insufficient patronising of public transport. They [9] suggested a maximum 300m distance of pedestrian travel to access public transport. A recent internationally-applicable suggestion [10] to apply this type of new technology to Brisbane's public transport system was rejected because of high retrofitting costs [11,12].…”
Section: Public Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…We must consider the need to reorganize society and generate an environmental power that ensures the maintenance of consumption of flows and capital in the long term. This implies further develop appropriate sustainability indicators [11].…”
Section: General Scheme For Sustainability In Urban Developmentmentioning
confidence: 99%